Framing Islam-related issues during GE13: an analysis of Malaysian mainstream newspapers - A.Manaf, Aini Maznina; Sedu, Nerawi (IIUM Press, 2015)
The two major political parties in Malaysia are Barisan Nasional and Pakatan Rakyat, which are dominated by the Malay-Muslim majority. During the 13th national election, to gain public votes, the government used mainstream newspapers to frame Islam-related issues. This research focuses on the characterisation and information reported about Islam and Muslims during the 13th General Election. Using content analysis, we examine the coverage of such issues by the mainstream newspapers: Berita Harian, Utusan Malaysia, New Straits Times, and The Star. This analysis aims to provide a holistic review of the scope of the coverage during the period with a focus on how the Malaysian government framed Islam-related issues through the print media in order to gain the Malay votes. A total of 178 news articles were analysed using content analysis from which we found that 15 dominant issues were reported in the newspapers during that period. Among the most frequently reported Islam-related issues were hudud (prescribed punishments), Islamic state, and kalimah Allah (the word “Allah”), which were predominantly covered by the Malay newspapers. In addition, the data indicated that most of the news were inclined towards supporting the ruling party, i.e., Barisan Nasional (BN).